REMOVAL OF DIRECT BLUE DYE IN TEXTILEWASTEWATER EFFLUENT BY ELECTROCOAGULATION (Journal of Engineering, 2024)
Removal of direct blue dye by electrocoagulation method has been investigated using aluminum electrode in a bench-scale electrochemical system. Current density, NaCl concentration, electrocoagulation time, and dye concentration has been studied as effecting parameters in color removal efficiency. Increasing of current density will increase the color removal efficiency and energy consumption as well. While increasing NaCl concentration increase the color removal efficiency but it decrease energy consumption. High dye concentration is needed for extra electrocaogolation time to reach the same efficiency that obtained with low dye concentration .With current applied 0.35 amps. and NaCl concentration of 2 g/l more than 93% efficiency achieved in 14 min. of electrocaogolation time.